Nexus to Lexis: Phonological Disorders in Children - Gierut, Judith A. (Semin Speech Lang, 2016)
Research on phonological disorders in children has conventionally emphasized the speech sound in search of causes, diagnoses, treatments and prevention of the disorder. This paper aims to shift the research focus to the word instead. The motivation comes from advances in psycholinguistics that demonstrate the word is central to the perception, production and acquisition of phonological information. Three strands of potential study are outlined in evaluation of how words might initiate and boost, but perhaps also, interrupt learning for children with phonological disorders.